2021
DOI: 10.3389/fonc.2021.709543
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Inhibits Proliferation and Promotes Myeloid Differentiation in TP53-Mutant Leukemia

Abstract: Loss-of-function mutations in the DNA demethylase TET2 are associated with the dysregulation of hematopoietic stem cell differentiation and arise in approximately 10% of de novo acute myeloid leukemia (AML). TET2 mutations coexist with other mutations in AML, including TP53 mutations, which can indicate a particularly poor prognosis. Ascorbate can function as an epigenetic therapeutic in pathological contexts involving heterozygous TET2 mutations by restoring TET2 activity. How this response is affected when m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Increased activity in vitro [101,112], in cell culture [101,102,114,117,120], in mice [121,122], and in a clinical setting [123] Regulation of haematopoiesis, mutations are a driver of leukaemia and other haematopoietic pathologies [95,121,[124][125][126].…”
Section: Tet2mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased activity in vitro [101,112], in cell culture [101,102,114,117,120], in mice [121,122], and in a clinical setting [123] Regulation of haematopoiesis, mutations are a driver of leukaemia and other haematopoietic pathologies [95,121,[124][125][126].…”
Section: Tet2mentioning
confidence: 99%
“…The relationship between vitamin C and TET activity has recently attracted attention in the context of leukaemia research, where vitamin C supplementation is being investigated as a form of epigenetic therapy to enhance TET2 activity in models of leukaemia characterised by decreased TET2 activity [95,121,122,124]. However, despite extensive research, the exact role of vitamin C in the TET catalytic cycle is unknown.…”
Section: Tet3mentioning
confidence: 99%
“…Regarding RCT trial, normalization of plasma vitamin C by oral supplementation leads to an increase in the 5hmC/5mC ratio compared to placebo-treated patients [ 114 ]. Vitamin C expressed anti-proliferative effects for AML cells with both TET2 and TP53 mutations [ 115 ]. However, currently, large scale clinical trial data are required to establish the clinical anti-proliferative effect of vitamin C in AML patients.…”
Section: Application Of Natural Products In Aml Therapymentioning
confidence: 99%
“…Clonal heterogeneity and metabolic heterogeneity are, in general, associated with the failure of anti-cancer drugs, including metabolic inhibitors [14][15][16]. However, the metabolic reprogramming occurring in AML hematopoietic stem cells depends on their genetic characteristics, and thus represents a promising target for treatment [17][18][19][20][21]. In this study, we compared the metabolic pathways underlying the different stages of differentiation of normal myeloid progenitors/precursors with that of primary blasts from six AML patients and of five AML cell lines featuring different genetic mutations commonly associated with AMLs, and diverse metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Hexokinase 1 and 2 (HK1/HK2) are also associated with the mitochondrial membrane permeability transition pore (PTP) and prevents apoptosis, thus controlling reactive oxygen species (ROS) formation [29]. Recent studies reported the capacity of ascorbate to target leukemia-initiating cells [20,21].…”
Section: Introductionmentioning
confidence: 99%